Design, synthesis, and evaluation of anxiolytic activity of 2-(4-phenylpiperazin-1-yl)-1H-benz[d]imidazole and 2-(4-phenylpiperazin-1-methyl)-1H-benz[d]imidazole derivatives - Mahajan, Bhavna Sunil; Kawale, Laxman A.; Nade, Vandana S.; Unavane, Supriya; Sajimon, Lida; Kapadnis, Prajakta (Future journal of pharmaceutical sciences, 2024)
Background In contemporary society, anxiety has become a widespread disorder leading to compromised well-being and heightened depressive states. Extensive literature reviews indicate the diverse biological effects of benzimidazole and piperazine derivatives, notably their impact on the central nervous system. This study aimed to design, molecularly dock, synthesize, and assess the anxiolytic potential of six derivatives of 2-(4-phenylpiperazin-1-yl)-1H-benz[d]imidazole and 2-(4-phenylpiperazin-1-methyl)-1H-benz[d]imidazole. Results In the present study, an attempt was made to synthesize benzimidazole derivatives conventionally. The benzimidazole nuclei are condensed with various substituted piperazines to obtain targeted benzimidazole–piperazine hybrids. Their anxiolytic activity is determined using the Elevated Plus Maze test and hole board test in mice. All compounds have shown good docking scores and in vivo anxiolytic activity. Conclusion Out of all the derivatives synthesized, compounds 5b, 5c, and 5f exhibited outstanding anxiolytic efficacy in both computational simulations and live subjects. Compound 5b demonstrated a remarkable docking score relative to the ligand, suggesting its potential as a promising candidate warranting further exploration.